The evolution of the wool and mohair marketing system in Lesotho: Implication for policy and institutional reform - Hunter, J.P.; Mokitimi, N.L. (International Livestock Centre for Africa, 1989)
For over eighty years, wool and mohair sales have provided Lesotho with its largest exports and with its largest domestically-generated sources of income. Presently, fleeces are marketed through any of three outlets: private traders, a government-sponsored marketing service, or, illegally, through smugglers. This marketing system has evolved in response to real or perceived problems with pre-existing systems. In addition to private sector marketing, Lesotho has experimented with co-operative societies, parastatal corporations, and government marketing/regulating departments. Evaluations of the efficiency and effectiveness of the present system suggest that there is room for additional adjustment and change. This paper outlines evaluations of the efficiency and effectiveness of the present wool and mohair marketing system in Lesotho and analyses and seeks to draw implications from them for continued institutional and policy reform.